Distinct co‐occurrence patterns of acculturation and perceived context of reception between weekdays and weekends among Hispanic college students. Issue 3 (26th September 2022) - Lee, Tae Kyoung; Meca, Alan; Schwartz, Seth J.; Cobb, Cory L.; Song, Hana; Duque, Maria; Stuart, Jaimee; Lorenzo‐Blanco, Elma I.
Abstract: Objective: The present study was designed to examine distinct co‐occurrence patterns of acculturation and perceived context of reception between weekdays and weekends among Hispanic college students in Miami and their influences on psychosocial maladaptation. Methods: We conducted a 12‐day diary study with a sample of first‐ and second‐generation Hispanic college students in Miami ( n  = 864). Depressive symptoms and physically aggressive behaviors were assessed on Days 1 and 12, and acculturation components and perceived negative context of reception were measured using single items on Days 2–11. We examined the overlap between weekday and weekend patterns of acculturation and negative context of reception, as well as links of this overlap with depressive symptoms and with physically aggressive behaviors. Results: Overall, six distinct co‐occurrence patterns of acculturation and perceived contexts of reception emerged from the analysis. Four of these appeared to represent stable co‐occurrence patterns regardless of weekdays and weekends and two indicated changing co‐occurrence patterns between weekdays and weekends. Students in patterns of the Moderate Biculturalism – High Negative Context of Reception regardless of weekdays and weekends reported high depressive symptoms and physically aggressive behaviors. Also, for the two changing co‐occurrence patterns, students in patterns of the Changes in both Acculturation and Negative Context of Reception between weekdays and weekends reported high scores on both depressive symptoms and physical aggressive behaviors. Conclusion: Both stable and changing patterns in acculturation and context of reception co‐occurrences between weekdays and weekends predicted psychosocial maladaptation.